'I left feeling different about myself': What students learn on their first practice placement. (February 2023) - Grant, Terri; Gossman, Peter; Thomas, Yvonne; Berragan, Liz; Frank, Helen
Introduction: With the inclusion of 40 hours of simulated practice education for UK occupational therapy students and the subsequent impact of the COVID-19 pandemic, universities have been exploring simulated placement opportunities. However, the evidence available to guide the development of such placements is sparse. This article presents the first stage of a grounded theory study that seeks to understand what students learn during the course of their first practice placement, with the intention of informing simulated placement development. Method: Grounded theory methodology was used to guide semi-structured individual interviews with 15 participants – seven undergraduate students, three practice educators and five postgraduate pre-registration students. Interviews occurred close to the end of the first practice placement. Concurrent data collection and analysis led to the development of categories of learning. Findings: Four core categories of learning were identified: learning about oneself, learning about the occupational therapy profession, learning about practices and learning about service users. Conclusion: Understanding of these four categories of learning may enable educators to consider learning which occurs that may not be anticipated, particularly in regard to personal development. This can enable educators to consider how learning can be targeted within simulation for an authentic simulated placement.